Konsep Pendidikan Karakter Dalam Tafsir Jalalain Dan Tafsir Al Ibriz - M. Faishol Sadli; Maftuh (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the concept of character education in Tafsir Jalalain and Tafsir Al-Ibriz based on the interpretation of Surah Luqman verses 12–19. The topic is essential because both works of tafsir contain universal and contextual moral teachings that can serve as foundations for building students’ noble character in contemporary Indonesia. The research aims to analyze and compare the concept of character education in both interpretations and to identify their relevance to Indonesia’s current character education system. This study employs a qualitative library research approach using content analysis to explore primary and secondary sources. The analysis focuses on interpreting textual meanings and contextual nuances in each tafsir to uncover values related to moral and character development.The findings reveal that both Tafsir Jalalain and Tafsir Al-Ibriz emphasize the development of human character in relation to God, oneself, others, and the surrounding environment. Tafsir Jalalain presents a more universal approach, while Tafsir Al-Ibriz offers local contextualization relevant to Indonesian culture. The two interpretations complement each other and remain highly relevant to strengthening character education in Indonesia today